Pelaksanaan Perjanjian Distributor Perusahaan Produsen Emas Di PT. Untung Bersama Sejahtera Surabaya - Andrian Fertila; Hayatul Ismi; Dasrol Dasrol (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
The appointment of a gold distributor is carried out through a distributor agreementcarried out by PT. Untung Bersama Sejahtera which is a limited liability company domiciledin the State of Surabaya Province of Indonesia, which manufactures and holds Patents for agold jewelry product of all sizes, shapes, colors and brands. PT. Untung Bersama Sejahterathen appoints distribution companies as distributors who are also limited liability companiesor individuals domiciled in Indonesia.The formulation of the problem in this study is twofold, namely First, how is theimplementation of the distributor agreement of the gold producer company at PT. fortunatelytogether prosperous Surabaya? Second, how is the legal protection of distributors who makedistributor agreements with gold producer companies at PT. fortunately together prosperoussurabaya?The conclusion of this study is 2, namely, First, Implementation of the distributoragreement of the gold producer company at PT. Untung Bersama Sejahtera Surabaya is thefirst 2 forms, the implementation of a distributor agreement verbally, where the verbalagreement was given directly by PT Untung Bersama Sejahtera Surabaya represented byHRD PT Untung Bersama Sejahtera namely Mr. Chess to the party who wanted to beappointed as gold distributor, at In 2007 there were 4 people who entered into a distributoragreement. Second, the implementation of the distributor agreement in writing / under thehand, where the agreement under the hand is immediately given by the chess pack as HRD ofPT Untun Bersama Sejahtera Surabaya, there are 2 people who make the distributoragreement. Second, legal protection against distributors who make distributor agreementswith gold producer companies at PT. Untung Bersama Sejahtera Surabaya is the first,preventive legal protection, where legal protection is in the form of counseling orsocialization of regulations governing the appointment of distributors. Second, repressivelegal protection, namely legal protection by government or law enforcement, whereproducers should not direct the person appointed to be a distributor to the local trade serviceto register the appointment of a distributor given sanctions, because if not then the personappointed does not get legal protection . Suggestions from this research are First, the goldproducer company in this research should be PT Unutng. Together with Sejahrtera carry outthe distributor agreement in the form of an authentic deed agreement at the notary andregister the distributor appointed to the local trade service. Second, the government shouldbe more detailed in drafting regulations regarding the appointment of distributors inIndonesia.Keywords: Implementation-Agreement of Producer-Distributor Companies.